Influence of Calcium Foliar Application to Increase Growth and Yield of Two Strawberry Cultivars (Fragaria x ananassa Duch.) - Parween Muhammad Kareem Rozbiany; Shler Mahmood Taha (Zanco Journal of Pure and Applied Sciences, 2020)
There are many studies about calcium effect on strawberry plants in the world, but few studies have been devoted to investigating its effects on strawberries in Kurdistan-Iraq. Strawberry, which has around twenty documented species, is native to Asia, Europe and South and North America. In the horticulture, it is considered the most important fruits. This research investigates the effect of spray of calcium on growth, flowering and yield of two strawberry cultivars (Fragaria X ananassa Duch.). Three different concentrations of Ca (0, 250 and 500 ppm) were applied by foliar method on two cultivars of strawberry (Festival and Albion). The results revealed a substantial increase in all the vegetative growth parameters at the level (500 ppm) of calcium for Alboin cultivar. However, the highest number of daughter plants was recorded at the level (250 ppm). while all flowering parameters increased significantly at the level (500 ppm) of calcium for Festival cultivar, significant increases were observed in the fruit parameters such as dry weight (g), dry weight percentage and fruit length (cm) at the level (500 ppm) of calcium for Alboin cultivar. Furthermore, it is monitored that fresh weight (g), fruit diameter (cm), fruit size (cm3), number of fruits, yield/plant (g) and yield/ha were increased significantly at the level (500 ppm) of calcium for Festival cultivar. Moreover, the highest value of fruit fall percentage was recorded at the control of Albion cultivar, conversely the lowest value was at control of Festival. The TSS and ascorbic acid were significantly elevated at the level (500 ppm) for Alboin cultivar, however, acidity percentage and sugar percentage raised significantly at the level (500 ppm) calcium for Festival cultivar. The biggest amount of vitamin C was acquired after storage of Festival cultivar that treated with (500 ppm) calcium, whereas the smallest amount was from the control group of Festival cultivar.